2007
DOI: 10.1111/j.1365-2036.2007.03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: proton pump inhibitor‐associated acute interstitial nephritis

Abstract: SUMMARY BackgroundA number of recent case reports and case series suggest that proton pump inhibitors may cause acute interstitial nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
107
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 38 publications
2
107
0
7
Order By: Relevance
“…In the present case, the possibility of AIN was initially considered because N-acetyl-β-D-glucosaminidase (NAG) and beta-2 microglobulin (β2-MG), markers of interstitial nephritis, were both elevated. However, in our study, potassium supplementation stabilized the NAG and β2MG levels to within the normal range without the need for glucocorticoid administration or hemodialysis, which is often required in the treatment of AIN induced by PPI (10). Furthermore, the NAG and β2MG levels were not elevated during the PPI challenge test.…”
Section: Discussionmentioning
confidence: 74%
“…In the present case, the possibility of AIN was initially considered because N-acetyl-β-D-glucosaminidase (NAG) and beta-2 microglobulin (β2-MG), markers of interstitial nephritis, were both elevated. However, in our study, potassium supplementation stabilized the NAG and β2MG levels to within the normal range without the need for glucocorticoid administration or hemodialysis, which is often required in the treatment of AIN induced by PPI (10). Furthermore, the NAG and β2MG levels were not elevated during the PPI challenge test.…”
Section: Discussionmentioning
confidence: 74%
“…As postulated by some researchers this can be attributed to idiosyncratic reaction. 1,12,19 It is possible to infer that if we would have stopped the drug at the first confirmed sign of deranged renal function, we could have seen reversal of the damage and confirmation of the postulate. 1,7 However since our aim was to first asses that the damage is produced and it is like AIN by HPE methodology, we accept this limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the electronic search study conducted by Sierra F et al, for articles written in between 1970-2006, studies with high level evidence (such as randomized trials) addressing the research question could not be found. 12 All of the information came from observational case reports and case studies that cannot control for confounding factors both known and unknown. 12 More than half of the samples of patients were on other medications capable of causing AIN, or had co-morbidities known to be risk factor for the development of renal failure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations